The Effectiveness of Combination Therapy of Foot Exercise and Warm Water Soak on Blood Glucose Level Reduction in Patients with Diabetes Mellitus - Azizah Khoirotun Ni’mah; Zaqqi Ubaidillah (International Journal of Health and Social Behavior, 2025)
Diabetes mellitus is a non-communicable disease that causes global health problems in society. The International Diabetes Federation predicts that the prevalence of diabetes worldwide will increase to 853 million by 2050. The increase in the number of diabetes patients is due to unhealthy lifestyle habits, such as lack of physical activity. Therefore, interventions such as foot exercises and warm water baths are needed to help control blood glucose levels. The purpose of this study was to determine the effectiveness of a combination of foot exercises and warm water baths in reducing blood glucose levels in patients with diabetes mellitus. The study design used a descriptive case study. The sample size was n=2 people, conducted from May 25, 2025, to May 27, 2025, in the Sukoanyar Village RT 03/RW 03 area, Pakis District, Malang City. The results of this study showed that after three consecutive days of intervention, there was a decrease in blood glucose levels in both research subjects. In Mrs. S, the initial GDS level of 360 mg/dl decreased to 240 mg/dl after the third day of intervention. Meanwhile, in Mr. D, the initial GDS level of 349 mg/dl decreased to 220 mg/dl after the same intervention. Thus, the combination therapy intervention of foot exercises and foot soaking in warm water can lower blood glucose levels in diabetes mellitus patients.